Gender analysis on the modes and extent of participation in community based fishery resource management (CFRM) projecet in Malalison island, Culasi, Antique - Benliro, Patriana ZP
A Gender Analysis on the Modes and Extent of Community Participation on CFRM in Malalison Island, Culasi, Antique was conducted in June 2002-February 2003. The study aimed to determine the modes and extent of participation in Community based Caostal Resource Management through the Community-based Fishery Resource Management (CFRM) Project using Program Monitoring with interview and focused group discussion. The difference on the modes and extent of participation of sex and membership in the association was also assessed. The study found out that male and female modes of participation in CFRM had no significant difference. The difference was in the extentof their participation, which was caused by the social roles they palyed. On the other hand membership in the organization was found to be a significant variable in analyzing the modes and extent of participation.